A questão ambiental na visão do camponês ilhéu no Assentamento Paulo Fonteles - Ilha de Mosqueiro, Belém - PA - COSTA, Laisa Tocantins Murta (2018)
The alarming problem involving coastal management of the Amazon biome needs discussions in order to be able the understanding of the set of fundamental causes of imbalances. Nevertheless, the region of the nearby islands of the metropolitan area of Belém, Pará, specifically the Mosqueiro Island, suffers from adversities generated by the inefficiency of managers and agencies institutions responsible for the command, logistics and administration of local resources. The most affected environment is generally rural, characterized by family production with shortages of infrastructure and assistance in general. This work is a socioenvironmental analysis through a native peasant perspective of a rural settlement called Paulo Fonteles, which is located on the island of Mosqueiro, administrative district municipality in Belém, Pará state, by implementing questionnaires to the population as well as the observation, record, analysis and classification of phenomena linked to coastal management natural resources. The population of this research can be defined as " Caboclo traditional " being mainly composed of elderly and adults with low education but with much empirical experience of countryside activities. There was a good correlation between the environmental perception of the respondents and the main environmental problems diagnosed, such as deforestation and disposal of solid waste. From this understanding, it is possible an identification of some variables socio-environmental reviews of the environment studied, facilitating the development of solutions of the adversities through the empowerment of local communities and social actors.